Implications Of Pressure And Range Of Motion On Posterior Fixation Of Thoracolumbar Burst Fractures - Marzuki, Nur Aimi Amanina Mohd (Universiti Sains Malaysia, 2019)
The surgical treatment for thoracolumbar burst fracture by using posterior construct is commonly practised respect to certain cases. Different cases have different spine fixation treatments which suitable to the patient condition and injury levels. Despite that, the consequence of those constructs is still less known on the biomechanics side. The purpose of this study is to analyse the effect of pressure on thoracolumbar spine fixation specifically on the tenth thoracic (T10) to the fifth lumbar (L5) due to implantation using posterior construct. Range of motion of the patient is studied to prevent excessive daily routines or activities that may affect the construction of the spine. A 3D model of thoracolumbar spine from thoracic 10 to lumbar 5 (T10 - L5) was used to evaluate the changes in the biomechanics of the spine segments. First, the model is obtained from the DICOM file of a patient which then extracted leaving the specified segments. Next, the model is imported in Ansys Transient Structural to analyse the changes. The model is validated on the von misses stress generated on the segments and the range of motion. The result showed the thoracic part of spine segment has low resistance towards pressure applied than lumbar area. According to pedicle construct, burst facture patient need to restrict the movement less than 30° of flexion to prolong the implantation life. Additionally, the pressure of 650 Pa exerted on the affected area has higher stress concentration and deformation than pressure at 450 Pa.